Prevalence of dental caries in patients treated at the Eloy Alfaro Lay University of Manabí - Cerón, Diego A.; Guillén, Ruth V. (Revista Gregoriana de Ciencias de la Salud, 2024)
The objective of this research was to determine the prevalence of dental caries in patients attending Dental Clinic III of the Dentistry Program at Universidad Laica Eloy Alfaro de Manabí (ULEAM) during the 2023-2 period. Dental caries represents a significant public health challenge in Ecuador, with a high incidence that affects the population’s quality of life. The main objective was to evaluate caries prevalence using the DMFT index (decayed, missing, and filled teeth), a standard in dental epidemiology. Additionally, the distribution of this index was analyzed according to variables such as age, gender, and nationality to identify risk groups and associated factors. The proposed methodology was a retrospective study with a non-experimental, retrospective cross-sectional design, in which data from 286 individuals were analyzed. Clear inclusion and exclusion criteria were established to ensure the validity of the results.